Miscellaneous new species in the “Cryptanthoid complex” (Bromeliaceae: Bromelioideae) from Eastern Brazil - Leme, Elton M.c.; Ribeiro, Otávio B.c.; Souza, Fernanda Vidigal D.; Souza, Everton Hilo De; Kollmann, Ludovic J.c.; Fontana, André P. (Phytotaxa, 2020)
The authors describe and illustrate 18 new species of the “Cryptanhoid complex”, encompassing the genera Cryptanthus (C. cruzalmensis, C. guanduensis, C. santateresinhensis, and C. univittatus), Forzzaea (F. coutensis, F. flavipetala, F. pseudomicra, and F. viridifolia), Hoplocryptanthus (H. knegtianus), Orthophytum subg. Orthophytum (O. alagoanum, O. brejoense, O. formosense, O. minimum, and O. santosianum), Orthophytum subg. Capixabanthus (O. arcanum), and Orthophytum subg. Clavanthus (O. cristaliense, O. gouveianum, and O. viridissimum). Besides, identification keys are provided for the first time for the species of the recently described genus Forzzaea and for Orthophytum subgenera Capixabanthus and Clavanthus.